The Effect of Ethical Climate and Locus of Control toward Whistleblowing Intention - David Pesudo; Cynthia Anakonda (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
This research purposes to determine the effect of the ethical climate principle and internal locus of control on whistleblowing intention. The population in this research were accounting students of the Faculty of Economics and Business, Satya Wacana Christian University, who already took auditing subjects. Collection data was carried out using questionnaires, and the data analysis technique used is multiple regression analysis. This study indicates that the ethical climate principle has a positive effect but does not significantly influence whistleblowing intention and internal locus of control has a positive effect on whistleblowing intention